Presentasi Oral O-077 s/d O-125 Hlm 161-250 - Jurnal Hemera Zoa (Hemera Zoa, 2016)
Presentasi Oral O-077 s/d O-125 Hlm 161-250 Prosiding KIVNAS Ke-14 PDHI 2016 di ICE, BSD City, Serpong, Tangerang Selatan.